Co–Cu–YSZ–GDC as an anode material for internal reforming SOFC?. Issue 2 (22nd November 2018) - Kumar, Selvaraj Senthil; Jayaram, Vikram; Ojha, Prasanta Kumar; Badi, Shri Prakash; Aruna, Singanahalli ThippaReddy
Abstract : A solid oxide fuel cell (SOFC) is a fuel-flexible device, and, apart from using pure hydrogen, it can utilize carbon monoxide, methane or any other higher hydrocarbons. Moreover, it can tolerate some degree of common fossil fuel impurities, such as ammonia and chlorides. It can even utilize the biogas derived from decomposable waste. However, the propensity of the state-of-the-art anode (nickel (Ni)–yttria-stabilized zirconia (YSZ)) toward carburization limits the ability of SOFCs to realize such a goal. In an attempt to develop a carbon-resistant anode system, the present work explores the carburization studies of a cobalt (Co)–copper (Cu) bimetallic anode system and fabrication of a cobalt–copper–YSZ–gadolinia-doped ceria (GDC) anode composite. The effect of alloying cobalt with copper and addition of rare-earth oxide on carburization has also been studied in detail. The anode composition was characterized for crystal structure, microstructure and redox stability. Using the optimized anode composition, SOFC single cells have been fabricated and their electrical and electrochemical performances have been evaluated. The investigated Co0·9 Cu0·1 YSZ0·95 GDC0·05 anode has undergone severe agglomeration during the fabrication and operation of the cell, which resulted in inferior performance. The surface-segregated copper acted as a poor catalyst for hydrocarbon oxidation.